The influence of human resources management practices on job performance among assistant registrars of Universiti Teknologi MARA / Mohd Zahurin Ramli - Ramli, Mohd Zahurin (2014)
21st millennium saw the world face many challenges arising from globalization, liberalization, internationalization and the development of information technology. This is also in the sample of higher education institutions including the University. Therefore, in order to become more effective and competitive, there is a need for educational institutions to make changes in the organization which includes aspects such as technology, structure, vision, mission, motivation and leadership and effective management orientation. Past studies prove that the practice of good human resource management is able to improve the performance of employees in line with the needs and goals of the organization. The question is, in a state institution of higher education that are often the foolish address a range of issues and challenges of national and global level, how much can the human resource administrators to enhance organizational performance and employee satisfaction as well as upkeep. Accordingly, the purpose of this study was to identify the perceptions of the assistant registrar of human resource management practices and their relationship to job performance at UiTM. This study is a cross-sectional field and nature. A total of 150 respondents were selected for this study consisted of the assistant registrar (grade N41 to grade N54 in UiTM Shah Alam. Researchers get feedback from the 91 respondents of the questionnaire. Results showed that there is a signifiken between human resource management and performance. Findings practical implications for policymakers , the registrar and the human resources manager where each human resource management planning for the systematic and fusion between human resource management practices and promote a sound strategy in order to make relevant and competitive institutions .